Design And Development Of An Early Childhood Development Monitoring And Reporting Information System Using The Web Development Life Cycle (WDLC)Method At Paud Kb Kenanga - Dhea Nova Ariska; Nuari Anisa Sivi; Rudi Hartono (Politeknik Siber Cerdika Internasional, 2026)
Continuous monitoring of early childhood development is essential to ensure that children's cognitive, motor, language, social, religious, emotional, and artistic development progresses according to established developmental milestones. However, the monitoring and reporting process at PAUD KB Kenanga, Raman Fajar Village, is still conducted manually using conventional notebooks, resulting in inefficient data management, difficulties in retrieving historical records, delayed information delivery, and limited parental access to children's developmental progress. Therefore, this study aims to design, develop, and evaluate a web-based Early Childhood Development Monitoring and Reporting Information System using the Web Development Life Cycle (WDLC) method. The study employed the WDLC approach consisting of planning, analysis, design and development, testing, implementation, and maintenance. Data were collected through observation, interviews, and documentation, while system functionality was evaluated using Black Box Testing involving Administrator, Teacher, and Parent access levels. The results demonstrate that the developed system effectively supports administrators in managing developmental data, enables teachers to record and report children's developmental progress digitally, and allows parents to monitor their children's development in real time through an online portal. All 32 Black Box Testing scenarios produced valid results (100%), indicating that the system functions as expected. The implementation of the proposed system improves the effectiveness, accuracy, continuity, and accessibility of developmental monitoring while strengthening communication between PAUD KB Kenanga and parents through an integrated web-based platform.